ОСНОВНЫЕ ОСОБЕННОСТИ РЕЛЬЕФА И ЭКЗОГЕННЫХ ГЕОМОРФОЛОГИЧЕСКИХ ПРОЦЕССОВ КУРИЛЬСКИХ ОСТРОВОВ (ПРОБЛЕМНЫЕ АСПЕКТЫ) - Короткий A.M.; Макарова Т.Р. (My University, 2006)
In the paper, special attention is paid to catastrophic processes like failures, rockfalls, landslides, mudflows, lahars, tsunamis, and storm-induced surges. The role of permafrost in the formation of mesorelief and its related deposits is examined. The reputed glacial deposits were formed by lahars, mudflows, and seismofalures. Eolian processes played significant role in the coastal relief formation during cold epochs in the Late Pleistocene and Holocene.
Keywords: 551.422(571.645); Кайнозой::Четвертичная::Голоцен; Кайнозой::Четвертичная::Плейстоцен